Perencanaan Partisipatif Dalam Program Sosialisasi Pusat Kegiatan Belajar Masyarakat - Salsabila, Nalasyahla; Damayanti, Inda Asri; Ramadhanti, Manda; Millah, Muhammad Saiful; Novitasari, Nastiti (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Community empowerment entails promoting and improving a community’s well-being by encouraging active engagement among its people. Community planning is one method of promoting empowerment. Bunter Village in the Sukadana sub-district is an excellent example of how participatory planning can empower the community. The local administration, the Community Learning Activity Centre (PKBM), and people are all involved in this project. The method used is participatory planning, with the goal of analyzing community involvement, notably in the June PKBM activities. This procedure provides the community with information and expertise to help them resume their education, which may have been postponed. The purpose of this socialization endeavor is to rekindle the community’s willingness to pursue non-formal education possibilities and to build a stronger sense of responsibility for education within the community.